Impact of Acadjas fisheries on fish assemblage in the Lake Nokoué, Bénin, West Africa. - LALEYE, PHILIPPE A. (My University, 2010)
Acadjas are artiﬁcial systems aimed at enhancing ﬁsh production by pro-viding additional substrata for development of plants and animals upon which the ﬁsh will feed. This study aims to evaluate the impact of acadjas on ﬁsh assemblages and on conservation of the ﬁsh fauna diversity in Lake Nokoué in Benin. Between June 2003 and September 2004, experimental acadjas were installed and monitored. Fish samples were obtained from two areas of Lake Nokoué (Ganvié and Zogbo stations) within and with-out acadjas with the assistance of artisanal ﬁshermen. Physico-chemical parameters were also measured inside and outside of the experimental acadjas in the same two stations. Twenty-ﬁve ﬁsh species belonging to 17 families were identiﬁed in acadjas out of a total of 51 species belong-ing to 34 families inventoried in 2001 at Lake Nokoué (i.e. 49% of the spe-ciﬁc richness of the ichthyofauna). Fifty-six percent of ﬁsh fauna caught in acadjas are estuarine forms and represent 78% of all estuarine forms of Lake Nokoué in 2001. The analysis of variance showed that the spe-ciﬁc richness of the acadjas varied signiﬁcantly according to the station (p < 0.05), with a high speciﬁc richness in Zogbo station where acadjas are less abundant. Acadjas are selective for some ﬁsh species such as cichlids which represent 95% of the total numeric abundance and con-tribute about 90% of the total ﬁsh biomass. The high densities of acad-jas could contribute to the reduction of the richness of ﬁsh fauna. Ratio-nal management could consist of reorganizing the surface areas of Lake Nokoué by preserving areas for other ﬁsh species that do not colonize acadjas
Keywords: Impact; pêcheries en acadjas; paramètres écologiques; assemblage